Differential Distribution of Geriatric Depression and Its Determinants in Community and Old-Age Homes of Mysore - Bhavani Nivetha M; Prashantha B; Mansoor Ahmed; Mudassir Azeez Khan; Rajagopal Rajendra (Medsci Publications, 2019)
Background: Mental disorders in the elderly are always overlooked and underdiagnosed. The most common neuropsychiatric disorders in this age group are dementia and depression. The geriatric depression variation with respect to different environments will help us to understand its epidemiology. Methods: To estimate and compare the prevalence of geriatric depression and the associated factors in community and old-age homes, a cross-sectional study was carried out in both these settings between august 2017 and april 2018. A sample of 150 was taken in community and old-age homes each. Cluster random sampling and simple random sampling were employed. Geriatric depression scale -15 (GDS-15) was used to assess the depression and mini-mental state examination (MMSE-30) was used to assess cognitive status. Results: Prevalence of geriatric depression in old-age home was 33.3% and in community was 31.2%, but the difference was not statistically significant (p=0.702). However in a subgroup analysis, prevalence of depression in private old-age home was 21.6% and public old-age home was 46.3% and this difference was statistically significant (p = 0.002). Age, marital status, education, socioeconomic status, economic dependency, source of pension, physical dependency and uncorrected hearing/visual impairment were the important predictors of depression. Conclusion: Prevalence of geriatric depression does not significantly vary in community and Old-age home, but it varies with respect to type of Old-age home. Better facilities and good environment in old-age homes may help to reduce depression.